A computational Evo-Devo approach for elucidating the roles of PLETHORA transcription factors in regulating root development - Joel Rodríguez-Herrera; Kenia Aislinn Galván-Alcaraz; Ramsés Uriel Albarrán-Hernández; Juan Pablo Villa-Núñez; Gustavo Rodríguez-Alonso; Svetlana Shishkova (PLoS ONE, 2025)
PLETHORA (PLT) transcription factors play essential roles in regulating various developmental processes in plants, including embryogenesis, rhizotaxis, phyllotaxis, and most prominently, root development, by regulating cell proliferation and differentiation along the root. Despite their important roles in plant development, PLT transcription factors have mainly been studied in Arabidopsis thaliana and only a few crop species. A. thaliana has six PLT genes, which are expressed in overlapping domains and have partially redundant activities, with numerous shared target genes. Here we identified putative PLT orthologs across Viridiplantae, including representatives of all extant plant clades, reconstructing the molecular phylogeny of PLTs and integrating synteny and microsynteny analyses. We suggest that PLTs arose by neofunctionalization prior to the divergence of Spermatophyta and that they might regulate their target genes in a context-specific manner given the presence of intrinsically disordered regions at their N- and C-termini. After identifying direct PLT targets in public databases, we inferred a gene regulatory network driven by PLTs in the root apical meristem in six angiosperm species. Our results suggest that the direct PLT targets regulate ribosome and ribonucleoprotein biogenesis as well as RNA processing, among other basic cellular processes. The central relevance of these processes may account for the high conservation and stability of PLT-driven gene regulatory networks across angiosperms.